Geology and Geotechnical Appraisal of Some Clay Deposits Around Ijero-Ekiti Southwestern Nigeria: Implication for Industrial Uses: Physical and Chemical Properties of Nigerian Clay (Biological Sciences - PJSIR, 2010)
The geotechnical appraisal of the clay deposits around Ijero-Ekiti, southwestern Nigeria, indicated that Ara and Ijero clays have 49.2% and 24.1% clay fractions, respectively, while Ilukuno variety has 32.8% clay fraction. The range of Atterberg liquid limits of Ara and Ijero clays was 41.8-48.0% and 25.6-36.5%, respectively, and those of plastic limits, 19.5-24.0% and 22.0-23.2%, respectively. XRD analyses showed kaolinite as the most prominent clay mineral present in the clays. Ara and Ijero clays were geochemically similar having SiO2, Al2O3, Fe2O3 concentrations, which reflect derivation from the underlying basement rocks. Thus, these clay deposits are suitable for the manufacture of paints, ceramics, refractories, agro-chemical and pharmaceutical products.